Macroeconomic stability and its Impact on GDP per capita: Evidence from selected African Countries - NZASABAYEZU, Onesme; Prakash, Senthil Kumar Jaya; Laxman, Vishnu; Guru, Satheesha; Rajagopalan, Kamal Kumar; Tiwari, Shiwani (Journal of Ecohumanism, 2024)
This study aims to investigate the macroeconomic stability factors that impact the GDP per capita in five selected African countries. These countries are Botswana, the Democratic Republic of Congo, Egypt, Nigeria and Rwanda. We used data collected from World Development Indicators from 1992 to 2022 and applied a multilinear regression model to analyze the data using SPSS 25. In Botswana, agriculture, industry, services, and total reserves, including gold and railway lines, significantly impact the GDP per capita with a P-value of 0.00 < 0.05. In DRC, services and Railways have a significant relationship with the GDP per capita with a P-value of 0.00< 0.05. In Egypt, industry and the rule of law significantly impact the GDP per capita with a P-value of 0.00 < 0.05. In Nigeria, the agriculture, industry, services, total reserves, including gold factors and the rule of law, have a significant relationship with the GDP per capita, with a P-value of 0.00 < 0.05. Finally, in Rwanda, agriculture, services and the rule of law have a significant relationship with GDP per capita, with a P-value of 0.00 < 0.05. Corruption and political instability are critical issues which hinder the selected African GDP per capita in all countries under study. Policymakers must control them.